Polyphenols, Flavonoids, and Antioxidant Activity Involved in Salt Tolerance in Wheat, Aegilops cylindrica and Their Amphidiploids - Kiani, Razieh; Arzani, Ahmad; Mirmohammady Maibody, S. A. M. (Frontiers in Plant Science, 2021)
Aegilops spp. is the closest genus to wheat (Triticum spp.), which makes Aegilops great candidates to exhibit precursors of wheat features. Aegilops cylindrica Host displays excellent salt tolerance. In the current study, biochemical and phytochemical compounds in the leaves of two wheat cultivars, one hyper-salt tolerant Ae. cylindrica genotypes and their amphidiploids (derived from ‘Chinese Spring’ × Ae. cilindrica and ‘Roshan’ × Ae. cylindrica), grown under control and saline field conditions, were assessed. These compounds included total protein content, proline content, electrolyte leakage, total flavonoid content, total phenolic content, DPPH radical scavenging activity and reducing power. In addition, phenolic components were also identified using HPLC analysis. Chlorogenic acid, ellagic acid, ferulic acid, syringic acid, vanillic acid, p-coumaric acid, caffeic acid, and gallic acid were the most abundant phenolic acids. Luteolin, apigenin, and rutin were the most abundant flavonoids in the leaves. Salt stress significantly increased all biochemical variables, with the exceptions of reducing power and p-coumaric acid. Interestingly, amphidiploid genotypes exhibited intermediate levels of most of the detected phenolic compounds between the two parental species. As demonstrated by bivariate correlations luteolin, chlorogenic acid, caffeic acid and apigenin could predict inhibition percentage by DPPH assay, suggesting a possible role in the cellular defense against oxidative stress in wheat. The amphidiploids and their wild parent performed significantly better than wheat cultivars on phenolic constituents, flavonoids, and maintaining redox homeostasis under salt stress conditions.